FUNGAL INVOLVEMENT IN BIOWEATHERING AND BIOTRANSFORMATION OF ROCKS AND MINERALS - Burford E.P.; Fomina M.; Gadd G.M. (My University, 2003)
In the Earth's lithosphere, fungi are of fundamental importance as decomposer organisms, animal and plant pathogens and symbionts (e.g. lichens and mycorrhizas), being ubiquitous in sub-aerial and subsoil environments. The ability of fungi to interact with minerals, metals, metalloids and organic compounds through biomechanical and biochemical processes, makes them ideally suited as biological weathering agents of rock and building stone. They also play a fundamental role in biogeochemical cycling of nutrients, (e.g. C, N, P and S) and metals (e.g. Na, Mg, Ca, Mn, Fe, Cu, Zn, Co and Ni) essential for the growth of living organisms in the biosphere. In addition they play an integral role in the mobilization and immobilization of non-essential metals (e.g. Cs, Al, Cd, Hg and Pb). Most studies on mineral-microbe interactions and microbial involvement in geological processes have concentrated on bacteria and archaea (Prokaryota): fungi (Eukaryota) have, to a certain extent, been neglected. This article addresses the role of fungi in geomicrobiological processes, emphasizing their deteriorative potential on rock, building stone and mineral surfaces and involvement in the formation of secondary mycogenic minerals. Such roles of fungi are also of importance for the global carbon reservoir and have potential biotechnological applications, e.g. in the bioremediation of xenobiotic-, metal- and/or radionuclide-contaminated soils and wastes, and metal/radionuclide recovery.